2021
DOI: 10.3390/toxics9030049
|View full text |Cite
|
Sign up to set email alerts
|

2,2-Bis(4-Hydroxyphenyl)-1-Propanol—A Persistent Product of Bisphenol A Bio-Oxidation in Fortified Environmental Water, as Identified by HPLC/UV/ESI-MS

Abstract: Biodegradation of bisphenol A in the environmental waters (lake, river, and sea) has been studied on the base of fortification of the samples taken and the biodegradation products have been analyzed using HPLC/UV/ESI-MS. Analysis of the characteristic fragmentation patterns of [M-H]− ions permitted unambiguous identification of the biodegradation products as 2,2-bis(4-hydroxyphenyl)-1-propanol or as p-hydroxyacetophenone, depending on the type of surface water source. The formation of 2,2-bis(4-hydroxyphenyl)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…HPLC-UV was also utilized as a reference by some authors that aimed to develop novel alternative methods for the determination of BPA [32][33][34]. Moreover, approximately a quarter of studies (23.64%) utilized HPLC-UV as a technique for quantification of BPA in environmental samples [35][36][37][38][39][40][41][42][43][44][45], mostly from aquatic habitats. 12.73% of the analyzed papers studied the leaching of BPA from consumer products, mostly dentistry resins [31,[46][47][48][49][50][51][52], but also from plastic packaging and bottles [53,54].…”
Section: Temporal Distribution and Purpose Of The Selected Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…HPLC-UV was also utilized as a reference by some authors that aimed to develop novel alternative methods for the determination of BPA [32][33][34]. Moreover, approximately a quarter of studies (23.64%) utilized HPLC-UV as a technique for quantification of BPA in environmental samples [35][36][37][38][39][40][41][42][43][44][45], mostly from aquatic habitats. 12.73% of the analyzed papers studied the leaching of BPA from consumer products, mostly dentistry resins [31,[46][47][48][49][50][51][52], but also from plastic packaging and bottles [53,54].…”
Section: Temporal Distribution and Purpose Of The Selected Articlesmentioning
confidence: 99%
“…The variety of these publications represents a reflection of the growing concerns in regard to BPA contamination. The literature search revealed that BPA was mostly identified in water samples [35,62] and sediment [63], but it could also contaminate soil via plastic trash and Fig. 3 A Main purpose of the analyzed studies as revealed by the publications in Table S1.…”
Section: Temporal Distribution and Purpose Of The Selected Articlesmentioning
confidence: 99%